Group portrait of the attendees of the Epworth League Insitute Conference in Humboldt - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of members of various Californian communities and churches, photographed during the Epworth League Insitute conference held in Humboldt, California, in June 1938.